1994
DOI: 10.1126/science.8197458
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor-Associated Proteins: Possible Mediators of Hormone-Induced Transcription

Abstract: The estrogen receptor is a transcription factor which, when bound to estradiol, binds DNA and regulates expression of estrogen-responsive genes. A 160-kilodalton estrogen receptor-associated protein, ERAP160, was identified that exhibits estradiol-dependent binding to the receptor. Mutational analysis of the receptor shows that its ability to activate transcription parallels its ability to bind ERAP160. Antiestrogens are unable to promote ERAP160 binding and can block the estrogen-dependent interaction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
311
1
4

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 597 publications
(324 citation statements)
references
References 31 publications
8
311
1
4
Order By: Relevance
“…Since this breast cancer cDNA encoded a nuclear receptor-binding auxiliary protein (Segars et al, 1993), we called the gene brx. Overlapping cDNA clones were consistent with a 5.3 kilobase cDNA encoding a 1428 amino acid protein with a 168 kilodalton predicted molecular mass distinct from proteins reported to bind nuclear hormone receptors (Cavailles et al, 1994(Cavailles et al, , 1995Halachmi et al, 1994;Jacq et al, 1994;Chen and Evans, 1995;Horlein et al, 1995;Onate et al, 1995;Le Douarin et al, 1995;Baniahmad et al, 1995).…”
Section: Identi®cation and Cloning Of Brx Cdnasupporting
confidence: 55%
See 1 more Smart Citation
“…Since this breast cancer cDNA encoded a nuclear receptor-binding auxiliary protein (Segars et al, 1993), we called the gene brx. Overlapping cDNA clones were consistent with a 5.3 kilobase cDNA encoding a 1428 amino acid protein with a 168 kilodalton predicted molecular mass distinct from proteins reported to bind nuclear hormone receptors (Cavailles et al, 1994(Cavailles et al, , 1995Halachmi et al, 1994;Jacq et al, 1994;Chen and Evans, 1995;Horlein et al, 1995;Onate et al, 1995;Le Douarin et al, 1995;Baniahmad et al, 1995).…”
Section: Identi®cation and Cloning Of Brx Cdnasupporting
confidence: 55%
“…For example, gene activation by nuclear hormone receptors (NHRs) has recently been shown to include additional proteins that associate directly with receptors, including the estrogen receptor (see : Horwitz et al, 1996;Katzenellenbogen et al, 1996). Biochemical and interactive cloning methods have led to isolation of 120 (Le Douarin et al, 1995), 125 (Onate et al, 1995), 140 (Cavailles et al, 1994(Cavailles et al, , 1995Halachmi et al, 1994), 160 (Halachmi et al, 1994;Cavailles et al, 1994), 168 (Chen and Evans, 1995) and 270 (Horlein et al, 1995) kDa proteins shown to associate with ligand-bound NHRs and function as positive (co-activators) or negative (corepressors) of nuclear receptor action by modulating interaction with the basal transcription complex. In addition, CBP (and related protein p300) has been described as a`co-integrator' of hormone receptor function through interaction with the nuclear receptor binding protein p160, TFIIB, and Jun/Fos (Kamei et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Possibly supporting this notion, Baniahmad et al (1995) recently mapped the silencing activity of TR to a region that includes a sequence corresponding to the C-terminal end of RXR 1 C2 and RXR 448. It is also possible that these truncated receptors are defective in interacting with mediators (Halachmi et al 1994;Cavailles et al 1995;Lee et al 1995) including recently reported corepressors (Horlein et al 1995;Chen & Evans 1995) with the basal trasncription factors Schulman et al 1995). Alternatively, truncated receptors might have 'squelched' a factor involved in activation by an abortive interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these effects are reversible by oestradiol (Lippman et al, 1986;Gottardis et al, 1988;Daly and Darbre, 1990). A recent report has suggested that the growth-inhibitory effects of tamoxifen may be explained in part by its ability to disrupt a complex between ER, ERAP160 (an ER-associated protein supposed to mediate oestradiol dependent transcriptional activation) and other factors necessary for transactivation (Halachmi et al, 1994). Consequently, ER-positive (ER+) breast cancer cells are more likely to respond to antioestrogen than ER-negative (ER-) breast cancer cells (Katzenellenbogen et al, 1985).…”
Section: Discussionmentioning
confidence: 99%